Analysis of the Influence of Leadership, Work Motivation and Teamwork on Employee Performance through Employee Retention as a Moderation Variable at PT Pelindo Regional I Dumai Branch - M. Aulia Arsyad; M. Chaerul Rizky; Kiki Farida Ferine (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of leadership, work motivation, and teamwork on employee performance through employee retention as a moderating variable at PT Pelindo Regional I Dumai Branch. The phenomenon underlying this research is the importance of improving employee performance to support the effectiveness of port operations in an increasingly competitive port industry era. This study uses a quantitative method with a survey approach. The population and sample of this research are all employees of PT Pelindo Regional I Dumai Branch, totaling 35 people using saturated sampling technique (census). The data collection technique uses a questionnaire with a Likert scale, and the data analysis technique uses Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS software to test direct effects and moderating effects. The results show that: (1) Leadership has a positive and significant effect on Employee Performance; (2) Work Motivation has a positive and significant effect on Employee Performance; (3) Teamwork has no significant effect on Employee Performance; (4) Employee Retention has a positive and significant effect on Employee Performance with the most dominant influence; (5) Employee Retention significantly moderates the effect of Leadership on Employee Performance; (6) Employee Retention does not moderate the effect of Work Motivation on Employee Performance; (7) Employee Retention significantly moderates the effect of Teamwork on Employee Performance. This research provides practical implications that the management of PT Pelindo Regional I Dumai Branch needs to prioritize employee retention strategies as the main foundation in improving organizational performance, followed by strengthening leadership quality, increasing work motivation programs, and improving effective teamwork systems.